Filosofi Puja Semadi dalam Serat Lokapala dan Shalat Istikharah sebagai Permintaan Petunjuk - Elisa Putriani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Puja Semadi and Shalat Istikharah are common religious practices. Puja Semadi is performed by Buddhists, while Shalat Istikharah is performed by Muslims. Both are done to ask for guidance from God. However, a few people do not understand correctly how to do it and as a result some people experience confusion and still doubt in obtaining the desired guidance. This research aims to find out how Puja Semadi in the lokapala fiber, and how the meaning of shalat istikharah as a request for guidance. This research uses qualitative methods and in-depth interviews with religious experts who understand shalat istikharah. Data were collected through text analysis and interviews, and analyzed using qualitative analysis with its procedures. The data on Puja Semadi was taken from the transliteration of ancient manuscripts. Initially, the Javanese script was transliterated into Latin and then translated into Indonesian. Based on the results of the research, Puja Semadi in the lokapala fiber is done through meditation in a place called pemujaan. While shakat istikharah is done anytime and anywhere as long as the place is clean and pure. The results of this study can help readers to understand how the explanation of Puja Semadi and Shalat Istikharah.